Prevalence Of Senile Cataract Among Aged Persons In Hills - Parvan U.C; Gupta B.p; Swami H.M; Ahluwalia S.K; Vaidya N.K (Wolters Kluwer Medknow Publications, 1986)
A study on the prevalence of senile cataract was carried out in urban and rural field practice areas of the Department of Preventive and Social Medicine, I.G. Medical College Shimla. All the persons aged 60 years and above were included in the survey, which was covered. There were 465 aged persons in the study population, of which only 406 could be examined. Senile cataract was present in 140 persons, thus the prevalence rate was 34.48%. The prevalence was higher in females and in the rural area.